Carbon materials, composite negative electrode materials and lithium-ion batteries

By using bowl-shaped structural carbon material and silicon-based composite anode material in lithium-ion batteries, the problems of high volume expansion rate and low volume energy density of silicon-based anode materials are solved, high capacity and good cycling performance are achieved, and the battery is extended life.

CN118651845BActive Publication Date: 2025-01-14BTR NEW MATERIAL GRP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411136285.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2025-01-14
Estimated Expiration
2044-08-19

AI Technical Summary

Technical Problem

The silicon-based anode material in existing lithium-ion batteries has a high volume expansion rate during charging and discharging, resulting in poor cycle life, and the cavities inside the carbon material reduce the volume energy density, making it difficult to take into account high capacity and good cycle performance.

Method used

Carbon materials with bowl-like structures are used to control the ratio of mesoporous, micropores and macropores, and the content of phosphorus and nitrogen is increased to form bowl-like structures to relieve volume expansion, and deposit active substances such as silicon in carbon materials to increase the negative electrode Specific capacity and cycle stability of the material.

Benefits of technology

The balance between volume energy density, capacity and cycling performance is achieved, the specific capacity and cycling stability of the negative electrode material are improved, and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118651845B_ABST
    Figure CN118651845B_ABST
Patent Text Reader

Abstract

The present invention discloses a carbon material, a composite negative electrode material and a lithium ion battery, and relates to the technical field of negative electrode materials and secondary batteries. The carbon material disclosed in the present invention has a bowl-shaped structure and has pores, wherein the pores include mesopores, and the pore volume of the mesopores accounts for ≥78% of the pore volume of the carbon material as 100%, and the total pore volume of the carbon material is 0.49~0.9 cm 3 / g. The present invention helps to increase the volume energy density of the negative electrode material prepared from the carbon material by regulating the structure of the carbon material. In addition, the inner and outer surfaces of the carbon material can be exposed to provide more active sites for the deposition of active substances such as silicon, and a certain buffer space can be provided for the expansion of active substances such as silicon, so that the negative electrode material prepared from the carbon material can achieve a balance between volume energy density, capacity and cycle performance, further expanding the application scope of the carbon material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials and secondary batteries, and in particular to a carbon material, a composite negative electrode material and a lithium ion battery. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, long cycle life, no memory effect and light weight, and are widely used in mobile phones, laptops, electric vehicles and other fields. With the development of science and technology, people's requirements for lithium-ion batteries are constantly increasing. In order to improve the energy density of batteries, silicon-based anode materials have received increasing attention. The specific capacity of silicon anodes is one order of magnitude higher than that of traditional graphite anodes, which is nearly ten times the storage capacity of graphite lithium. However, despite the excellent theoretical capacity of silicon anodes, their cycle life is poor, and their limited cycle life is mainly caused by the volume expansion of silicon during lithiation. After full lithiation, the volume expansion of silicon is as high as 300%, resulting in the pulverization and failure of the anode material, and even detachment from the current collector, causing irreversible structural damage and performance degradation. At present, various silicon structures and silicon-carbon-based composites have been studied to reduce the stress caused by lithiation and inhibit the structural damage of silicon.

[0003] Constructing a three-dimensional porous structure to protect silicon is an effective strategy to improve the electrochemical performance of composite materials. For example, constructing a 3D hollow porous nanosphere structure can increase the interlayer spacing, which is conducive to the insertion and deinsertion of lithium ions, has faster transmission kinetics, and can provide more sites for silicon deposition, providing more space for its volume expansion. However, the huge cavity inside the 3D hollow porous nanosphere structure will reduce the volume energy density. Therefore, it is urgent to provide a new carbon material to solve the problem that negative electrode materials are difficult to have good volume energy density, capacity and cycle performance. Summary of the invention

[0004] The main purpose of the present invention is to provide a carbon material, a composite negative electrode material and a lithium ion battery to solve the problem in the prior art that carbon materials are difficult to have both high silicon loading and high volume energy density.

[0005] In order to achieve the above object, according to a first aspect of the present invention, a carbon material is provided, wherein the carbon material has a bowl-shaped structure and has pores; wherein the pores include mesopores, and the pore volume of the mesopores of the carbon material accounts for ≥ 78% based on the pore volume of the carbon material as 100%; and the total pore volume of the carbon material is 0.49-0.9 cm 3 / g.

[0006] Furthermore, the carbon material has micropores, and based on the total pore volume of the carbon material being 100%, the pore volume of the micropores of the carbon material accounts for ≤13%.

[0007] Furthermore, the carbon material has macropores, and based on the total pore volume of the carbon material being 100%, the pore volume of the macropores of the carbon material accounts for ≤10%.

[0008] Furthermore, the specific surface area of ​​carbon materials is 75~90 m 2 / g.

[0009] Furthermore, the average pore size of the carbon material is 5~8 nm.

[0010] Furthermore, the thickness of the carbon material is 108~135 nm.

[0011] Furthermore, the carbon material contains phosphorus, and the mass fraction of the phosphorus is 7.6% to 10.6% based on the mass fraction of the carbon material being 100%;

[0012] Furthermore, the carbon material contains nitrogen element. Taking the mass fraction of the carbon material as 100%, the mass fraction of the nitrogen element is 7.8% to 8.9%.

[0013] Furthermore, the carbon material includes at least one of artificial graphite, natural graphite, amorphous carbon, activated carbon, mesophase carbon microbeads, carbon nanotubes, carbon nanofibers, and graphene.

[0014] According to a second aspect of the present invention, there is provided a composite negative electrode material, which comprises the carbon material according to the first aspect of the present invention and an active substance, wherein the active substance is at least partially located in the pores of the carbon material.

[0015] Furthermore, the active material includes at least one of Li, Na, K, Sn, Ge, Si, Fe, Mg, SiO, Ti, Zn, Al, P, and Cu.

[0016] Furthermore, the active material includes a silicon-based material, and the silicon-based material includes at least one of amorphous silicon, crystalline silicon, a composite of crystalline silicon and amorphous silicon, silicon oxide, and a silicon alloy.

[0017] Furthermore, taking the mass fraction of the composite negative electrode material as 100%, the mass fraction of silicon element is 35% to 50%.

[0018] Furthermore, the pore volume of the carbon material is 2.5 to 8.5 times the pore volume of the composite negative electrode material.

[0019] Furthermore, the mesopore volume of the carbon material is 4 to 16 times the mesopore volume of the composite negative electrode material.

[0020] Furthermore, the average pore size of the composite negative electrode material is 2.0~4.5 nm.

[0021] Furthermore, the specific surface area of ​​the composite negative electrode material is 160~185 m 2 / g.

[0022] Furthermore, the total pore volume of the composite negative electrode material is 0.1~0.18 cm 3 / g.

[0023] According to a third aspect of the present invention, a lithium ion battery is provided. The lithium ion battery comprises the carbon material according to the first aspect of the present invention and the composite negative electrode material according to the second aspect of the present invention.

[0024] By applying the technical solution of the present invention and controlling the carbon material to have a bowl-shaped structure, the volume expansion of the negative electrode material during the charge and discharge process can be alleviated to a certain extent, and the cycle performance can be improved. At the same time, compared with the 3D hollow porous nanosphere structure, the bowl-shaped structure has relatively fewer internal cavities, which helps to reduce the volume energy density of the negative electrode material. In addition, by regulating the pore structure of the carbon material, more silicon can be loaded on the carbon material, which helps to increase the specific capacity of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a scanning electron microscope image of the carbon material in Example 2;

[0026] Figure 2 is a scanning electron microscope image of the carbon material in Example 3;

[0027] Figure 3 This is a scanning electron microscope image of the carbon material in Comparative Example 1;

[0028] Figure 4 This is a scanning electron microscope image of the carbon material in Comparative Example 4;

[0029] Figure 5 is a pore size distribution diagram of the carbon material in Example 3;

[0030] Figure 6 This is the pore size distribution diagram of the composite negative electrode material in Example 13. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0032] As described in the background of the present invention, the existing silicon-based composite materials have high expansion rate and poor cycle performance during charging and discharging, and the carbon materials used to load silicon have huge internal cavities, which will reduce the volume energy density of the negative electrode material. In order to solve the above technical problems, in a typical embodiment of the present invention, a carbon material is provided, which is a bowl-shaped structure with pores, wherein the pores include mesopores, and the pore volume of the carbon material is 100%, and the pore volume of the mesopores of the carbon material accounts for ≥78%, which can be 78%, 80%, 82%, 85%, 86%, etc., or other values ​​within this range, which are not specifically limited here; the total pore volume of the carbon material is 0.49~0.9 cm 3 / g, specifically 0.49 cm 3 / g, 0.51 cm 3 / g, 0.6 cm 3 / g, 0.7 cm 3 / g, 0.8 cm 3 / g, 0.9 cm 3 / g, etc., and may also be other values ​​within this range and are not particularly limited herein.

[0033] In the description of the present invention, the term "bowl-like structure" refers to a bowl-like shape having a concave bottom and a certain height around it.

[0034] Compared with the hollow spherical structure, the present invention limits the carbon material to a bowl-shaped structure, which can reduce the volume of the cavity on the one hand, improve the volume energy density of the negative electrode material prepared from the carbon material, and expose the inner and outer surfaces of the carbon material on the other hand, providing more active sites for the deposition of active substances such as silicon, and also providing a certain buffer space for the expansion of active substances such as silicon, so that the negative electrode material prepared from the carbon material can achieve a balance between volume energy density, capacity and cycle performance, so that the carbon material has a wider range of applications. Controlling the total pore volume of the carbon material helps to increase the deposition amount of active substances in the negative electrode material prepared from the carbon material, and improve the specific capacity of the negative electrode material. In addition, the total pore volume of the carbon material is controlled within an appropriate range, which can improve the compressive strength of the carbon material and improve its processing performance. The mesopores in the carbon material are conducive to the filling of active substances such as silicon particles, so that the active substances can be uniformly filled in the pores of the carbon material, and the capacity of the composite negative electrode material prepared from the carbon material is improved. In addition, the expansion of the active substances can be effectively alleviated, and the cycle stability of the composite negative electrode material prepared from the carbon material can be improved.

[0035] In some embodiments, the carbon material has micropores, and the pore volume of the carbon material is 100%, and the pore volume of the micropores is ≤13%, which can be 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 13%, etc., or other values ​​within the range, which are not specifically limited here. By controlling the pore volume ratio of the micropores, on the one hand, the wettability of the electrolyte can be improved, and on the other hand, it is conducive to the deposition of active materials such as silicon in the pores, thereby improving the capacity and cycle stability of the negative electrode material.

[0036] In some embodiments, the carbon material has macropores, and the pore volume of the macropores is ≤10% based on the pore volume of the carbon material as 100%, and can be 4%, 5%, 6%, 8%, 10%, etc., or other values ​​within this range, which are not particularly limited here. Controlling the pore volume proportion of macropores in the carbon material is beneficial to uniformly distribute the active substance on the carbon material on the one hand, and to improve the processing performance of the carbon material on the other hand.

[0037] In the description of the present invention, the term "micropore" refers to a pore with a pore size less than 2 nm, the term "mesopore" refers to a pore with a pore size of 2 to 50 nm, and the term "macroporous" refers to a pore with a pore size of 50 to 150 nm.

[0038] In some embodiments, based on the total pore volume of the carbon material as 100%, the pore volume of the mesopores accounts for 80% to 86%, the pore volume of the micropores accounts for 3% to 11%, and the pore volume of the macropores accounts for 7% to 10%. By optimizing the pore volume ratios of the mesopores, micropores, and macropores, on the one hand, more active sites can be provided for the deposition of active substances on the carbon material, and on the other hand, it is beneficial to improve the wettability of the electrolyte on the negative electrode material made of the carbon material, thereby increasing the capacity of the negative electrode material.

[0039] In some embodiments, the carbon material contains phosphorus, and the mass fraction of the phosphorus is 7.6% to 10.6%, specifically 7.6%, 8.0%, 8.4%, 8.8%, 9.4%, 10.0%, 10.5%, etc., and may be other values ​​within the range, which are not specifically limited here. In addition to helping to form a hollow bowl-shaped carbon material, adding phosphorus provides more deposition sites for active materials such as silicon, and also helps to improve the first coulombic efficiency of the negative electrode material.

[0040] In some embodiments, the carbon material contains nitrogen, and the mass fraction of the nitrogen is 7.8% to 8.9%, specifically 7.8%, 8.0%, 8.3%, 8.6%, 8.9%, etc., based on the mass fraction of the carbon material as 100%, and may be other values ​​within the range, which are not limited here. Adding nitrogen helps to improve the conductivity and stability of the negative electrode material.

[0041] In some embodiments, the specific surface area of ​​the carbon material is 75 to 90 m 2 / g, specifically 79 m 2 / g, 82 m 2 / g, 85 m 2 / g, 90 m 2 Controlling the specific surface area of ​​the carbon material helps to improve the contact area between the negative electrode material prepared from the carbon material and the electrolyte, and enhances the ion transport performance of the negative electrode material prepared from the carbon material.

[0042] In some embodiments, the average pore size of the carbon material is 5 to 8 nm, specifically 5.2 nm, 5.5 nm, 6 nm, 6.5 nm, 7 nm, 7.5 nm, 8 nm, etc., or other values ​​within the range, which are not limited here. Controlling the average pore size of the carbon material helps to improve the active material loading capacity of the carbon material.

[0043] In some embodiments, the average thickness of the carbon material is 108-135 nm, where the thickness of the carbon material refers to the thickness of the shell of the bowl-shaped carbon material. Ten carbon material particles are randomly selected using a scanning electron microscope for thickness measurement, and the average value is the average thickness of the material. By controlling the thickness of the carbon material, on the one hand, the stability of the negative electrode material can be improved and its cycle performance can be improved, and on the other hand, it is beneficial to shorten the ion transmission distance and increase the ion transmission rate.

[0044] Typically, but not limiting, the carbon material includes at least one of artificial graphite, natural graphite, amorphous carbon, activated carbon, mesophase carbon microbeads, carbon nanotubes, carbon nanofibers, and graphene.

[0045] In a typical embodiment of the present invention, a method for preparing a carbon material is provided, comprising the following steps:

[0046] Prepare a carbon coating layer on the surface of polystyrene microspheres to obtain carbon-coated microspheres;

[0047] The carbon-coated microspheres and the phosphorus-containing substance are dispersed in a solvent, ground, dried and calcined to obtain a carbon material.

[0048] Using polystyrene microspheres as templates, a spherical carbon coating can be formed. Through calcination and doping with phosphorus, polystyrene decomposes, and the spherical structure of the carbon coating collapses locally, forming a bowl-shaped carbon material with a concave bottom, and the pore volume ratio of its mesopores increases. Compared with spherical carbon materials, bowl-shaped carbon materials can provide more active sites, allowing active substances such as silicon particles to be deposited on the carbon material, thereby increasing the capacity of the negative electrode material prepared from the carbon material.

[0049] In another typical embodiment of the present invention, a composite negative electrode material is provided. The composite negative electrode material includes the carbon material in the above embodiment of the present invention and an active substance loaded on the carbon material, and the active substance is at least partially located in the pores of the carbon material.

[0050] In some embodiments, the active material includes at least one of Li, Na, K, Sn, Ge, Si, Fe, Mg, SiO, Ti, Zn, Al, P, and Cu.

[0051] In some embodiments, the morphology of the active material includes at least one of a dot shape, a sphere shape, an ellipsoid shape, and a flake shape.

[0052] In some embodiments, the active material includes a silicon-based material, and the silicon-based material includes at least one of amorphous silicon, crystalline silicon, a composite of crystalline silicon and amorphous silicon, silicon oxide, and silicon alloy. For example, amorphous silicon expands isotropically during lithium insertion, which can reduce pore collapse, inhibit the rapid attenuation of the specific capacity of the negative electrode material, and is more conducive to improving the lithium insertion cycle performance of the negative electrode material.

[0053] In some embodiments, the purity of the active material is greater than 99%. Taking silicon-based materials as active materials as an example, high-purity silicon-based materials are more conducive to Li-Si alloying with lithium, thereby improving the cycle performance of lithium-ion batteries.

[0054] In some embodiments, the average particle size of the silicon particles in the composite negative electrode material is 0.1 to 50 nm, for example, it can be 0.1 nm, 1 nm, 10 nm, 20 nm, 30 nm or 50 nm, etc., or other values ​​within this range, which are not specifically limited here. Within the above-defined range, it is beneficial to buffer the stress and deformation generated by the silicon particles during the process of lithium ion insertion and extraction, and improve the capacity and cycle performance of the composite negative electrode material. Preferably, the average particle size of the silicon particles is 1 nm to 5 nm, specifically 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, etc., or other values ​​within this range, which are not specifically limited here. By controlling the average particle size of the silicon particles, the expansion rate of the composite negative electrode material during the charge and discharge process can be reduced, and the cycle performance of the composite negative electrode material can be improved.

[0055] In some embodiments, the mass fraction of the composite negative electrode material is 100%, and the mass fraction of the silicon element is 35% to 50%, specifically 35%, 38%, 40%, 42%, 45%, 49%, etc., or other values ​​within the range, which are not limited here. The mass fraction of the silicon element within the above range can effectively improve the capacity of the composite negative electrode material.

[0056] In some embodiments, the pore volume of the carbon material is 2.5 to 8.5 times the pore volume of the composite negative electrode material, preferably 4.5 to 8.5 times, specifically 4.5 times, 5 times, 5.5 times, 6 times, 7 times, 8 times, etc., and may also be other values ​​within this range, which are not limited here. By controlling the relationship between the pore volume of the carbon material and the pore volume of the composite negative electrode material, the deposition sites of active substances such as silicon particles in the carbon material are mainly in the pores, and in addition, there is enough space in the composite negative electrode material to buffer the expansion of the active substances, which is beneficial to improving the cycle performance of the composite negative electrode material.

[0057] In some embodiments, the mesopore volume of the carbon material is 4 to 16 times the mesopore volume of the composite negative electrode material.

[0058] By controlling the pore volume relationship between the mesopores of the carbon material and the composite negative electrode material, the active material such as silicon particles is mainly deposited in the mesopores of the composite negative electrode material, so that the composite negative electrode material has a higher capacity and capacity retention rate.

[0059] In some embodiments, the micropore volume of the carbon material is 0.9 to 1.71 times the micropore volume of the composite negative electrode material.

[0060] In some embodiments, the macropore volume of the carbon material is 0.5 to 4.2 times the macropore volume of the composite negative electrode material.

[0061] By controlling the pore volume relationship between micropores and macropores of carbon materials and composite negative electrode materials, the electrochemical performance of composite negative electrode materials can be further improved.

[0062] In some embodiments, the average pore size of the composite negative electrode material is 2.0-4.5 nm, specifically 2.0 nm, 2.4 nm, 2.8 nm, 3.2 nm, 3.5 nm, 4 nm, 4.5 nm, etc., or other values ​​within the range, which are not limited here. By controlling the average pore size of the composite negative electrode material, on the one hand, it is beneficial to the deintercalation of lithium ions, and on the other hand, it is beneficial to release the stress generated by the volume expansion of the active material in the composite negative electrode material during the charge and discharge process.

[0063] In some embodiments, the specific surface area of ​​the composite negative electrode material is 160-185 m 2 / g, specifically 160m 2 / g, 165 m 2 / g, 170 m 2 / g, 175 m 2 / g, 180 m 2 / g, 185 m 2 / g, etc., and may also be other values ​​within this range, which are not limited here. Controlling the specific surface area of ​​the composite negative electrode material can effectively control the contact area between the composite negative electrode material and the electrolyte, which is beneficial to improving the ion transmission rate during the charge and discharge process.

[0064] In some embodiments, the total pore volume of the composite negative electrode material is 0.1 to 0.18 cm 3 / g, specifically 0.1cm 3 / g, 0.11 cm 3 / g, 0.12 cm 3 / g, 0.14 cm 3 / g, 0.18 cm 3 / g, etc., and may also be other values ​​within this range, which are not limited here. When the total pore volume of the composite negative electrode material is within the above range, it can provide protection for the expansion of active materials such as silicon, reduce its pulverization rate, and improve the comprehensive electrochemical performance of the composite negative electrode material; in addition, it can also improve the compressive strength of the negative electrode material during the process of making the electrode sheet, thereby improving the processing performance of the negative electrode material.

[0065] In a typical embodiment of the present invention, a method for preparing a composite negative electrode material is provided, comprising the following steps:

[0066] Prepare a carbon coating layer on the surface of polystyrene microspheres to obtain carbon-coated microspheres;

[0067] The carbon-coated microspheres and the phosphorus-containing substance are dispersed in a solvent, ground, dried, and calcined to obtain a carbon material having a bowl-shaped structure;

[0068] Active materials are deposited on the carbon material to obtain a composite negative electrode material.

[0069] In the description of the present invention, “on the carbon material” refers to the surface of the carbon material and / or the inside of the pores of the carbon material.

[0070] The above preparation method is simple and can produce a composite negative electrode material with good cycle performance and high capacity, which is suitable for industrial application.

[0071] In some embodiments, the method for preparing the composite negative electrode material specifically comprises the following steps:

[0072] Dispersing a surfactant and polystyrene microspheres in a first solvent and performing surface modification treatment to obtain surface-modified polystyrene microspheres;

[0073] dispersing the surface-modified polystyrene microspheres in a second solvent to obtain a surface-modified polystyrene microsphere suspension;

[0074] The nitrogen-containing monomer is dispersed in a suspension of surface-modified polystyrene microspheres, and an oxidant is used to cause oxidative polymerization on the surface of the surface-modified polystyrene microspheres, followed by washing and drying to obtain nitrogen-doped carbon-coated microspheres; the nitrogen-containing monomer is at least one of pyrrole, polyacrylonitrile, melamine formaldehyde resin, polyvinyl pyrrolidone, and dopamine;

[0075] Dispersing nitrogen-doped carbon-coated microspheres and phosphorus-containing substances in a third solvent, grinding, drying, and calcining to obtain a carbon material containing nitrogen elements;

[0076] Active materials are deposited on the carbon material to obtain a composite negative electrode material.

[0077] By doping with nitrogen, the conductivity of the composite negative electrode material can be improved, which helps to improve the charge and discharge rate of the battery.

[0078] In some embodiments, the surface modification treatment is performed at a temperature of 70-80° C. and for a time of 3-5 h.

[0079] In some embodiments, the phosphorus-containing substance is at least one of phytic acid, red phosphorus, and sodium dihydrogen phosphate; and / or the oxidant is at least one of Fe(NO3)3, Sn(NO3)4, SnCl4, and FeCl3; and / or the surfactant is at least one of sodium dodecyl sulfate, dodecylbenzene sulfonic acid, and anionic polyacrylamide; and / or the first solvent and the second solvent are each independently a mixed solvent of water and an organic solvent, wherein the organic solvent is at least one of ethanol, methanol, ethyl acetate, xylene, and n-hexane; and / or the third solvent is an organic solvent, such as at least one of acetone, propylene glycol, and glycerol.

[0080] In some embodiments, the average particle size of the polystyrene microspheres is 300-400 nm.

[0081] The use of polystyrene microspheres with the above diameters can produce carbon materials of a desired size, which is beneficial to improving the capacity of the composite negative electrode material.

[0082] In some embodiments, the mass ratio of polystyrene microspheres to the first solvent is (0.5-5):100; the mass ratio of polystyrene microspheres to the surfactant is (1-50):1; and the volume ratio of the organic solvent to water in the first solvent is (2-4):(7-9).

[0083] Under the above conditions, the polystyrene microspheres can be evenly distributed in the first solvent, and the surfactant can be fully adsorbed on the surface of the polystyrene microspheres, which is beneficial to the subsequent polymerization of the nitrogen-containing monomer on the surface.

[0084] The mass ratio of the surface modified polystyrene microspheres to the second solvent is (1-5):200; the volume ratio of the organic solvent to water in the second solvent is 1:(10-100).

[0085] Under the above conditions, the surface-modified polystyrene microspheres can be uniformly dispersed in the second solvent to form a surface-modified polystyrene microsphere suspension, which is conducive to the formation of a uniform polymer coating layer on the surface of the nitrogen-containing monomer.

[0086] In some embodiments, the oxidative polymerization and calcination processes are performed under an inert atmosphere, which includes nitrogen, argon or a mixture thereof.

[0087] In some embodiments, during the oxidative polymerization process, the mass ratio of the nitrogen-containing monomer to the oxidant is (8-20): 100. Under the above conditions, the nitrogen-containing monomer can fully undergo polymerization reaction.

[0088] In some embodiments, the mass ratio of nitrogen-doped coated microspheres to phosphorus-containing substances is 1:(1-3).

[0089] By controlling the mass ratio of the two, the carbon material can have a certain bowl-shaped structure and a suitable pore structure, providing more active sites for the deposition of active substances such as silicon particles.

[0090] In some embodiments, the mass ratio of nitrogen-doped carbon-coated microspheres to the third solvent is (20-30):100.

[0091] In some embodiments, the calcination temperature is 300-1100° C., and the calcination time is 2-10 h. When calcined under the above conditions, phosphorus can be doped into the carbon material, and it is beneficial to form a carbon material with a bowl-shaped structure.

[0092] In some embodiments, a vapor phase silicon source is vapor deposited on a carbon material to obtain a composite negative electrode material.

[0093] Vapor deposition is a commonly used deposition method that can decompose a vapor-phase silicon source and then deposit it on solid particles. It has high deposition efficiency, strong controllability, and good uniformity.

[0094] In some embodiments, the vapor-phase silicon source includes at least one of monosilane, disilane, dichlorosilane, and trichlorosilane.

[0095] In some embodiments, the temperature of vapor deposition is 500-650° C., and the time of vapor deposition is 1-10 h.

[0096] When the deposition is carried out under the above conditions, the deposition amount of active substances such as silicon particles on the carbon material is moderate, which is beneficial to increasing the capacity of the composite negative electrode material and improving the cycle performance of the composite negative electrode material.

[0097] In some embodiments, during the vapor deposition process, the flow rate of the vapor silicon source is 20-100 sccm.

[0098] In some embodiments, an auxiliary carrier gas is added during the vapor deposition process, the auxiliary carrier gas includes at least one of nitrogen, helium, and argon, and the flow rate of the auxiliary carrier gas is 50-200 sccm.

[0099] In some embodiments, the flow ratio of the gas-phase silicon source and the auxiliary carrier gas is (5-80): (50-200).

[0100] In some embodiments, after mixing the carbon material and the active substance and subjecting them to heat treatment, the method further comprises: mixing the heat-treated material and the coating material and subjecting them to heat treatment.

[0101] In some embodiments, the coating material includes at least one of a carbon source, a metal oxide, and a nitride.

[0102] In some embodiments, the sulfide includes at least one of tin sulfide, molybdenum sulfide, titanium sulfide, iron sulfide, and copper sulfide.

[0103] In some embodiments, the metal oxide includes at least one of iron oxide, zinc oxide, tin oxide, copper oxide, and titanium oxide.

[0104] In some embodiments, the carbon source includes at least one of a gaseous carbon source and a solid carbon source.

[0105] In some embodiments, the gaseous carbon source includes at least one of acetylene, methane, propylene, benzene, ethanol, methanol, ethylene, propane, and butane.

[0106] In some embodiments, the flow rate of the gaseous carbon source is 0.1~1000 L / min, specifically 0.1 L / min, 1 L / min, 10 L / min, 100 L / min, 300 L / min, 600 L / min and 1000 L / min, etc., and of course it can also be other values ​​within the above range, which is not limited in this application.

[0107] In some embodiments, the solid carbon source includes at least one of sucrose, fructose, glucose, asphalt, phenolic resin, polyimide, citric acid, epoxy resin, amino resin, polystyrene, polyacrylic acid, carboxymethyl cellulose, and cellulose acetate butyrate.

[0108] In some embodiments, the mass ratio of the solid carbon source to the material obtained by heat treatment is (1~100):100, specifically 1:100, 10:100, 30:100, 50:100, 80:100, 100:100, etc., and of course it can also be other values ​​within the above range, which is not limited in this application.

[0109] In some embodiments, the temperature of the heat treatment is 600-1100°C. Specifically, the temperature of the heat treatment can be, for example, 600°C, 650°C, 700°C, 800°C, 900°C, 1000°C, 1000°C, etc. Of course, it can also be other values ​​within the above range, and the present application is not limited here. If the temperature of the heat treatment is lower than 600°C, the carbonization of the coating material is incomplete, and a dense coating layer cannot be obtained. If the temperature of the heat treatment is higher than 1100°C, the silicon material is crystallized, resulting in poor cycle performance and expansion performance of the negative electrode material.

[0110] In some embodiments, the holding time of the heating treatment is 2 to 10 hours. Specifically, the holding time of the heating treatment can be, for example, 2 hours, 5 hours, 7 hours, 8 hours, 10 hours, etc., and of course, it can also be other values ​​within the above range, which is not limited in the present application.

[0111] In some embodiments, after the heat-treated material and the coating material are mixed and heated, the method further includes: screening and grading the obtained material.

[0112] In another typical embodiment of the present invention, a lithium-ion battery is provided. The lithium-ion battery comprises the carbon material or composite negative electrode material in the above embodiment.

[0113] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0114]

Carbon materials

[0115] Example 1

[0116] An embodiment of the carbon material of the present invention, the preparation method of the carbon material in this embodiment is as follows:

[0117] (1) 6 g of polystyrene microspheres (particle size of 300-400 nm) were dispersed in 160 mL of a mixed solution of anhydrous ethanol and deionized water (volume ratio of 3:8), 0.2 g of sodium dodecyl sulfate was added, and the mixture was stirred at 75 °C in a water bath for 4 h. Surface-modified polystyrene microspheres were obtained by centrifugation and drying.

[0118] (2) 5 g of surface-modified polystyrene microspheres were dispersed in a mixed solution of 50 mL of anhydrous ethanol and 500 mL of deionized water, and the microspheres were evenly dispersed by ultrasonication for 1 h to form a suspension of surface-modified polystyrene microspheres;

[0119] (3) Using nitrogen to remove oxygen from the surface-modified polystyrene microsphere suspension, stirring continuously, taking 4.2 mL of pyrrole monomer and adding it to the surface-modified polystyrene microsphere suspension, and adding 50 mL of FeCl3 aqueous solution with a concentration of 0.7 g / mL, and polymerizing for 48 h. Then, the reaction product was washed several times with deionized water and anhydrous ethanol, and dried in an oven to obtain a carbon material containing nitrogen element;

[0120] (4) Disperse 3 g of nitrogen-containing carbon material and 4.5 g of phytic acid in 60 mL of acetone. After stirring for 3 h, place the mixed sample in a sand mill and grind and stir for 1 h. Dry it and place it in a tubular furnace. Under nitrogen protection, heat it from room temperature to 800 °C over 7 h, keep it at this temperature for 2 h, and finally cool it naturally to room temperature. Take out the calcined product to obtain the carbon material.

[0121] Example 2

[0122] An embodiment of the carbon material of the present invention, the preparation method of the carbon material in this embodiment is different from that in embodiment 1 only in that: in step (4), the amount of phytic acid used is 5.25 g.

[0123] Example 3

[0124] An embodiment of the carbon material of the present invention, the preparation method of the carbon material in this embodiment is different from that in embodiment 1 only in that: in step (4), the amount of phytic acid used is 6 g.

[0125] Example 4

[0126] An embodiment of the carbon material of the present invention, the preparation method of the carbon material in this embodiment is different from that in embodiment 1 only in that: in step (4), the amount of phytic acid used is 6.75 g.

[0127] Example 5

[0128] An embodiment of the carbon material of the present invention, the preparation method of the carbon material in this embodiment is different from that in embodiment 1 only in that: in step (4), the amount of phytic acid used is 7.5 g.

[0129] Example 6

[0130] An embodiment of the carbon material of the present invention, the preparation method of the carbon material in this embodiment is different from that in embodiment 3 only in that: in step (3), the amount of pyrrole monomer used is 4.9 mL.

[0131] Example 7

[0132] An embodiment of the carbon material of the present invention, the preparation method of the carbon material in this embodiment is different from that in embodiment 3 only in that: in step (3), the amount of pyrrole monomer used is 5.6 mL.

[0133] Example 8

[0134] An embodiment of the carbon material of the present invention, the difference between the preparation method of the carbon material described in this embodiment and that of Example 1 is that in step (3), 13g of polyvinyl alcohol is added to the surface-modified polystyrene microsphere suspension, and the mixture is continuously stirred and then placed in an oven to dry to obtain a pretreated carbon material; in step (4), the nitrogen-containing carbon material is replaced by the pretreated carbon material.

[0135] Example 9

[0136] An embodiment of the carbon material of the present invention, the preparation method of the carbon material in this embodiment is different from that in embodiment 1 in that, in step (4), the grinding and stirring time is 0.5 h.

[0137] Example 10

[0138] An embodiment of the carbon material of the present invention, the preparation method of the carbon material in this embodiment is different from that in embodiment 1 in that, in step (4), the grinding and stirring time is 2 hours.

[0139] Comparative Example 1

[0140] A carbon material, which is different from Example 1 only in that, in step (4), the amount of phytic acid used is 3 g.

[0141] Comparative Example 2

[0142] A carbon material, which is different from Example 1 only in that, in step (4), the amount of phytic acid used is 3.75 g.

[0143] Comparative Example 3

[0144] A carbon material, which is different from Example 1 only in that in step (4), the amount of phytic acid used is 8.25 g.

[0145] Comparative Example 4

[0146] A carbon material, which is different from Example 1 only in that in step (4), the amount of phytic acid used is 9 g.

[0147] Comparative Example 5

[0148] A carbon material, which is different from Example 1 only in that in step (3), the amount of pyrrole monomer used is 2.8 mL.

[0149] Comparative Example 6

[0150] A carbon material, which is different from Example 1 only in that in step (3), the amount of pyrrole monomer used is 8.4 mL.

[0151]

Composite negative electrode materials

[0152] Examples 11-20 and Comparative Examples 7-12

[0153] Examples 11-20 are respectively composite negative electrode materials made of the carbon materials in Examples 1-10, and Comparative Examples 7-12 are respectively composite negative electrode materials made of the carbon materials in Comparative Examples 1-6. The preparation method of the composite negative electrode materials is:

[0154] The carbon material was placed in a rotary tube furnace, and high-purity monosilane gas (purity of 99.99%) was continuously introduced at a flow rate of 60 sccm and flowed at 550 °C for 2 hours to obtain a composite negative electrode material.

[0155] Performance Testing

[0156] (1) Morphology: The surface morphology of carbon materials was observed using a Japanese JSM-7610FPlus scanning electron microscope;

[0157] (2) Structure: Using the Lihua Lianke iPore620 pore size tester and BET pore size distribution test method, the isothermal adsorption characteristic curve of nitrogen was used to obtain the pore size distribution data of the material through DFT simulation analysis, and then the average pore size, pore volume and BET specific surface area of ​​the material were obtained;

[0158] (3) Average thickness of carbon material: the average value of 10 carbon shell thicknesses measured according to the ruler of the SEM image;

[0159] (4) Element content: XPS test was performed using the X-ray photoelectron spectrometer PHI VersaProbe4 from ULVAC-PHI of Japan;

[0160] (5) Electrochemical performance: The composite negative electrode material was mixed with conductive carbon black (super P) and aqueous binder (LA133) in a mass ratio of 91:3:6 to form a slurry and evenly coated on a copper foil. After drying, the slurry was prepared into electrode sheets, which were assembled into button cells and tested for capacity, coulombic efficiency and cycle performance on a Blue Electric battery test cabinet M340A at a rate of 1C.

[0161] Figure 1~2 They are respectively the scanning electron microscope images of the carbon materials in Examples 2 to 3, Figure 3~4 The scanning electron microscope images of the carbon materials in Comparative Examples 1 and 4 are shown. As can be seen from the images, the carbon materials in the present invention all have a concave bottom, that is, a bowl-shaped structure, while the bowl-shaped structure is no longer observed in the carbon materials in Comparative Examples 1 and 4. Figure 5 is the pore size distribution diagram of the carbon material in Example 3, Figure 6 is the pore size distribution diagram of the composite negative electrode material in Example 13; Figures 5 and 6 It can be found that silicon in the composite negative electrode material is mainly located in the mesopores of the carbon material.

[0162] Table 1 is the performance test results of the carbon material, Table 2 is the performance test results of the composite negative electrode material, and Table 3 is the electrochemical performance test results of the composite negative electrode material.

[0163] Table 1

[0164]

[0165] Table 2

[0166]

[0167] Table 3

[0168]

[0169] As shown in Table 3, the first coulombic efficiency of the batteries prepared with the composite negative electrode materials in Examples 11 to 20 is higher than 87%, and the charge mass specific capacity is higher than 1800 mAh / g, and the charge volume specific capacity is higher than 360 mAh / cm 3 , the charge capacity retention rate after 500 cycles is higher than 83%, and it has good electrochemical performance. The composite negative electrode materials described in Comparative Examples 7 to 10 are prepared from the carbon materials described in Comparative Examples 1 to 4, and the micropore volume accounts for a high proportion, while the mesopore volume accounts for a low proportion, resulting in a low silicon deposition amount of the composite negative electrode materials in Comparative Examples 7 to 10, and the charge mass specific capacity and charge volume specific capacity are significantly lower than those in Examples 11 to 20. The carbon material used in Comparative Example 11 has a high proportion of micropore volume and a low total pore volume, and the carbon material used in Comparative Example 12 has a high proportion of micropore volume, resulting in poor electrochemical performance of the batteries prepared in Comparative Examples 11 to 12.

[0170] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A composite negative electrode material, characterized in that: The invention comprises a carbon material and an active substance, wherein the carbon material is a bowl-shaped structure and has pores, wherein the pores include mesopores, micropores and macropores, and the active substance is at least partially located in the pores of the carbon material; based on the pore volume of the carbon material being 100%, the pore volume of the mesopores of the carbon material accounts for ≥78%, the pore volume of the micropores of the carbon material accounts for ≤13%, and the pore volume of the macropores of the carbon material accounts for ≤10%; the total pore volume of the carbon material is 0.49-0.9 cm 3 / g; the carbon material contains phosphorus, and the mass fraction of the phosphorus is 7.6%~10.6% based on the mass fraction of the carbon material as 100%; the specific surface area of ​​the carbon material is 75~90 m 2 / g.

2. The composite negative electrode material according to claim 1, characterized in that: The carbon material comprises at least one of the following features: (1) The average pore size of the carbon material is 5-8 nm; (2) The thickness of the carbon material is 108-135 nm.

3. The composite negative electrode material according to claim 1, characterized in that: The carbon material contains nitrogen element. Taking the mass fraction of the carbon material as 100%, the mass fraction of the nitrogen element is 7.8% to 8.9%.

4. The composite negative electrode material according to claim 1, characterized in that: The active material includes at least one of Li, Na, K, Sn, Ge, Si, Fe, Mg, SiO, Ti, Zn, Al, P, and Cu.

5. The composite negative electrode material according to claim 1, characterized in that: The active material includes a silicon-based material, and the silicon-based material includes at least one of amorphous silicon, crystalline silicon, a composite of crystalline silicon and amorphous silicon, silicon oxide, and a silicon alloy.

6. The composite negative electrode material according to claim 5, characterized in that: Taking the mass fraction of the composite negative electrode material as 100%, the mass fraction of silicon in the composite negative electrode material is 35% to 50%.

7. The composite negative electrode material according to claim 1, characterized in that: The composite negative electrode material includes at least one of the following features: (1) The pore volume of the carbon material is 2.5 to 8.5 times the pore volume of the composite negative electrode material; (2) The mesopore volume of the carbon material is 4 to 16 times the mesopore volume of the composite negative electrode material; (3) The average pore size of the composite negative electrode material is 2.0-4.5 nm; (4) The specific surface area of ​​the composite negative electrode material is 160~185 m 2 / g; (5) The total pore volume of the composite negative electrode material is 0.1~0.18 cm 3 / g.

8. A lithium ion battery, characterized in that: The composite negative electrode material comprises any one of claims 1 to 7.

Citation Information

Patent Citations

  • Nano silicon-oxygen-carbon composite material as well as preparation method and application thereof

    CN116525776A